2012
DOI: 10.4028/www.scientific.net/amm.233.374
|View full text |Cite
|
Sign up to set email alerts
|

Analysis about the Jointing Status for Dissimilar Metals of Steel with Magnesium

Abstract: The research status of welding process between magnesium with steel have been surveyed.This article detailed the laser welding, Laser-TIG hybrid welding, pressure welding,diffusion brazing. The paper pointed out that it is a prominent problem of magnesium to be oxidated easily and existing intermetallic compound in the joint, which will produce adverse effect to property of welded joint. So how to control morphology and existence state of intermetallic compound (IMC) is the key for quality connectors in joinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The analysis of the strengthening mechanism revealed that with the addition of suitable interlayers, the joint shear strength could reach a significantly high value or even surpasses Mg alloy BM. Generally, the corrosion behavior of magnesium alloys is affected by the microstructural variation imposed by welding process [27,43,56,63,64,125,126,131]. For similar Mg/Mg welds, the grain refinement imposed by welding process was reported to improve the corrosion resistance [132].…”
Section: Laser Beam Weldingmentioning
confidence: 99%
“…The analysis of the strengthening mechanism revealed that with the addition of suitable interlayers, the joint shear strength could reach a significantly high value or even surpasses Mg alloy BM. Generally, the corrosion behavior of magnesium alloys is affected by the microstructural variation imposed by welding process [27,43,56,63,64,125,126,131]. For similar Mg/Mg welds, the grain refinement imposed by welding process was reported to improve the corrosion resistance [132].…”
Section: Laser Beam Weldingmentioning
confidence: 99%